Timing is Everything: PTTH Mediated DHR4 Nucleocytoplasmic Trafficking Sets the Tempo of Drosophila Steroid Production - Rewitz, Kim F.; O'Connor, Michael B. (Frontiers in Endocrinology, 2011)
During development multicellular organisms must become sexually mature to reproduce. But what underlying developmental clock times this transition? Recent data shows that in fly larvae, nuclear-cytoplasmic trafficking of DHR4, a nuclear receptor, in response to Prothoraciotropic hormone (PTTH) signaling is critical for producing the correct temporal pulses of steroid hormones that coordinate the juvenile-adult transition.